2011
DOI: 10.1038/eye.2011.269
|View full text |Cite
|
Sign up to set email alerts
|

Individualised patient care as an adjunct to standard care for promoting adherence to ocular hypotensive therapy: an exploratory randomised controlled trial

Abstract: Purpose To evaluate the impact of individualised patient care, as an adjunct to standard care, on adherence to ocular hypotensive therapy. Methods A two-arm, single-masked exploratory randomised controlled trial recruited patients newly prescribed ocular hypotensive therapy. The intervention involved an individual assessment of health-care needs and beliefs and a 1-year follow-up period according to need. The primary outcome was refill adherence, measured by collating prescription and dispensing data for 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 43 publications
3
65
0
1
Order By: Relevance
“…Previous research recognizes that clients who receive emotional support and information at the initial diagnosis of glaucoma benefit by subsequently displaying good compliance and cooperation with their care (7,8). The NICE Guideline Development Group made recommendations for research into the clinical effectiveness of providing people with glaucoma with a glaucoma personal record (GPR) and for this to be compared to standard treatment (9).…”
Section: You May Notmentioning
confidence: 99%
“…Previous research recognizes that clients who receive emotional support and information at the initial diagnosis of glaucoma benefit by subsequently displaying good compliance and cooperation with their care (7,8). The NICE Guideline Development Group made recommendations for research into the clinical effectiveness of providing people with glaucoma with a glaucoma personal record (GPR) and for this to be compared to standard treatment (9).…”
Section: You May Notmentioning
confidence: 99%
“…In the UK, Gray and colleagues 17 randomized 127 newly diagnosed patients with ocular hypertension or open angle glaucoma from a single eye hospital in England to a personalized individual healthcare assessment in addition to standard care or standard care with an ophthalmologist. The intervention began with a 75 minute counseling session with a glaucoma nurse to design a one year personalized follow-up plan.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, five out of the nine RCTs used electronic medication monitoring. 14,16,20,21,22 Two RCTs, Gray's study 17 of individualized counseling with a glaucoma nurse and Muir's of education tailored to health literacy, used medication refill data. This is also a widely accepted measure of medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies using multifaceted intervention components including education and discussing strategies for incorporating medication administration into their daily activities have detected a significant improvement in adherence [138,139]. Patients who have a stronger belief in the necessity for eye drops are more adherent [140], and studies that have targeted patient beliefs have been effective in improving adherence [141,142]. The study by Gray and co-workers found a positive improvement in adherence to glaucoma medication using an individualised patient care programme, which included education and training with the patient and their informal caregivers [142].…”
Section: Age-related Comorbiditiesmentioning
confidence: 97%
“…Patients who have a stronger belief in the necessity for eye drops are more adherent [140], and studies that have targeted patient beliefs have been effective in improving adherence [141,142]. The study by Gray and co-workers found a positive improvement in adherence to glaucoma medication using an individualised patient care programme, which included education and training with the patient and their informal caregivers [142]. Whilst it is not possible to ascertain the individual components of the complex intervention that may have improved adherence behaviour, modelling patient care according to the healthcare needs and beliefs about medicines could hold the key to the design of future interventions.…”
Section: Age-related Comorbiditiesmentioning
confidence: 99%